Plant cultural indicators of forest resources from the Himalayan high mountains: implications for improving agricultural resilience, subsistence, and forest restoration - Haq, Shiekh Marifatul; Khoja, Aadil Abdullah; Waheed, Muhammad; Pieroni, Andrea; Siddiqui, Manzer H.; Bussmann, Rainer W. (Journal of ethnobiology and ethnomedicine, 2024)
Aim Biocultural legacy practices are intricately tied to forestry resources, ethnic identity, and social cohesiveness. This study aims to determine the plant cultural values of forest resources and identify plant cultural indicators in each ethnic group, which can aid in long-term natural resource management plans in the current debate on socio-environmental and ecological transitions. Methods Semi-structured interviews, focus group discussions, and field observations were employed to collect data for a comprehensive and systematic ethnobotanical survey from February 2018 to October 2022. Results A total of 330 informants reported 154 plant species from 65 families. Asteraceae was the most prominent botanical family, with herbaceous plant groups outnumbering trees and shrubs. The Gujjar and Pahari groups exhibited the highest level of overlap, followed by significant overlaps between the Gujjar and Kashmiri communities. The close affinity observed between the Gujjar and Pahari groups suggests the horizontal pattern of local plant knowledge between these communities, influenced by their sociocultural interactions and intermarriages. Notably, the Pahari community displayed a rich understanding of medicinal plants and shared unique uses for the reported taxa. This study affirms that both ecological factors and sociocultural influences have played significant roles in shaping local plant knowledge. A total of 31 plant species have been identified as plant cultural markers among all four ethnic groups. We observed a positive correlation between plant cultural values and plant use with the Gujjar and Kashmiri ethnic groups. Artemisia absinthium reported the highest use value of (0.57) with use reports of (189). Adonis aestivalis, Cynoglossum nervosum, Geum elatum, Geranium himalayense, Juncus inflexus, Oxalis acetosella, Polygonatum biflorum, and Salvia hians from the Himalayan region are among the plant taxa whose ethnomedicinal applications are described here for the first time. Conclusion Our data show that local and indigenous forest knowledge and practices could significantly contribute to forest conservation and ecological transition. This may happen if stakeholders generate clear frameworks and biocultural conservation strategies aimed at both dynamically preserve natural habitats and ways of traditional management of local natural resources.